(untitled) (Revista Inclusiones, 2020)
The changes occurring in the socioeconomic structure impact the development of higher education and the transition from industry 3.0 to industry 4.0 determined the goal of the education as the transformation from the educational process into a business process. The formation of a new approach to the processes of the university allows evaluating in details the results of the university. The ultimate goal of the study is to increase the effectiveness of the university. From the point of view of the process approach, educational activity is the main business process. In the case of statefinanced places, the main clients of this business process are the state and society. The state directly (through financing) and society indirectly (through paid taxes) invest in training future personnel who, in accordance with their educational direction, must participate in the creation of the gross product. Currently, according to various surveys, less than 70 percent of graduates are employed.